Photoinduced Copper‐Catalyzed Asymmetric Three‐Component Coupling of 1, 3‐Dienes: An Alternative to Kharasch–Sosnovsky Reaction. Issue 42 (9th September 2021) - Wang, Peng‐Zi; Wu, Xue; Cheng, Ying; Jiang, Min; Xiao, Wen‐Jing; Chen, Jia‐Rong
Abstract: Kharasch–Sosnovsky reaction is one of the most powerful methods for allylic oxidation of alkenes. However, the inherent radical mechanism and use of peroxides as both oxidants and oxygen nucleophiles render dearth of universal catalytic systems for highly enantioselective variants and limited scope. Herein, an alternative to the asymmetric Kharasch–Sosnovsky reaction that utilized a chiral copper catalyst and purple‐LED irradiation to enable the three‐component coupling of 1, 3‐dienes, oxime esters, and carboxylic acids is reported. This protocol features mild conditions, remarkable scope and functional group tolerance as evidenced by >80 examples and utility in the late‐stage modification of pharmaceuticals and natural products. Detailed mechanistic studies provide evidences for the radical‐based reaction pathway. Abstract : An alternative to the asymmetric Kharasch–Sosnovsky reaction that utilized a chiral copper catalyst and purple‐LED irradiation to enable the three‐component coupling of 1, 3‐dienes, oxime esters, and carboxylic acids is reported. This protocol features mild conditions, remarkable scope and functional group tolerance as evidenced by >80 examples and utility in the late‐stage modification of pharmaceuticals and natural products.